Advances in Hepatology - Rodrigo, Luis; Martins, Ian; Guo, Xiaozhong; Qi, Xingshun (IntechOpen, 2021)
This book discusses clinical advances in hepatology, with a focus on metabolic diseases and chronic hepatitis C. The development of direct-acting antiviral (DAA) agents for the treatment of hepatitis C virus (HCV) infection in 2010 has completely transformed the management of this disease. This transformative nature of DAA therapy underpins the goal of the World Health Organization (WHO) to eliminate HCV infection as a public health threat by 2030. The advantages of using these therapies include high efficacy (sustained virological response rate >95%) with minimal side effects, good tolerability, easy drug administration (once-daily oral dosing) and short duration of treatment (8-12 weeks). The commercialization of second-generation DAA agents due to their high effectiveness, few side-effects and pangenotypic action. This transformative nature of DAA therapy underpins the goal of the WHO to eliminate HCV infection as a public health threat by 2030.